Kulturen der Lehrerbildung in der Sekundarstufe in Italien und Deutschland Nationale Formate und ,cross culture' - Casale, Rita; Windheuser, Jeannette; Ferrari, Monica; Morandi, Matteo (Historische Bildungsforschung, 2021)
From an educational-historical view this book analyses the cultural models that underlie the conception and organisation of secondary teacher education and the professionalisation of future secondary school teachers in Europe. Based on different conceptions of school, citizenship and the teaching profession these models have an enormous influence on school policy. Taking the examples of Italy and Germany, the complex history of teacher education is reconstructed and analysed. The various articles deal in a long-term view with the emergence of national models of teacher education at the end of the 18th century, their consolidation in the 19th and 20th centuries and their transnational transformation between past and present.